2021
DOI: 10.1038/s41598-021-85483-0
|View full text |Cite
|
Sign up to set email alerts
|

Exact dimer phase with anisotropic interaction for one dimensional magnets

Abstract: We report the exact dimer phase, in which the ground states are described by product of singlet dimer, in the extended XYZ model by generalizing the isotropic Majumdar–Ghosh model to the fully anisotropic region. We demonstrate that this phase can be realized even in models when antiferromagnetic interaction along one of the three directions. This model also supports three different ferromagnetic (FM) phases, denoted as x-FM, y-FM and z-FM, polarized along the three directions. The boundaries between the exact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 75 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…The spin model lies in the dimer phase for α = J 2 /J 1 0.25 [15][16][17]. The increase of the antiferromagnetic nextnearest coupling coefficient J 2 enables the formation of dimers [20]. We show that shared purity and concurrence (a measure of bipartite entanglement) of a mixture of ground and low-lying excited states detect this spin fluid to dimer quantum phase transition.…”
Section: Introductionmentioning
confidence: 81%
“…The spin model lies in the dimer phase for α = J 2 /J 1 0.25 [15][16][17]. The increase of the antiferromagnetic nextnearest coupling coefficient J 2 enables the formation of dimers [20]. We show that shared purity and concurrence (a measure of bipartite entanglement) of a mixture of ground and low-lying excited states detect this spin fluid to dimer quantum phase transition.…”
Section: Introductionmentioning
confidence: 81%
“…The spin model lies in the dimer phase for α = J 2 /J 1  0.25 [17][18][19]. The increase of the antiferromagnetic nextnearest coupling coefficient J 2 enables the formation of dimers [22]. We show that shared purity and concurrence (a measure of bipartite entanglement) of the pseudo-thermal state detect this spin fluid to dimer quantum phase transition.…”
Section: Introductionmentioning
confidence: 81%
“…Quantum phase transitions take place at absolute zero temperature, when some external parameter or coupling strength is varied [1,4,65]. The quantum phase transition of the one-dimensional antiferromagnetic J 1 −J 2 model from a gapless fluid to gapped dimer phase driven by the change of the system parameter α was investigated in [66][67][68][69] using exact digonalisation and field theory formalism. It was found that the phase transition occurs around a critical value of the parameter, α c ≈ 0.241.…”
Section: Introductionmentioning
confidence: 99%